Selected styles in web-based educational research - Mann, Bruce Leslie, 1950- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2006)
This book is concerned with the most common research styles in Web-based teaching or learning. It is intended for practitioners, educators and students, who wish to learn how to conduct research in online teaching and learning, and helps define style in educational research methodology. To enhance understanding, the writing style is conversational with detailed learning objectives, activities, procedures and illustrations to help the reader understand several common research styles.